2020
DOI: 10.7150/jca.41942
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC00467 Promotes Glioma Progression through Inhibiting P53 Expression via Binding to DNMT1

Abstract: This study aimed to investigate whether long noncoding RNA (lncRNA) LINC00467 could regulate proliferative and invasive abilities of glioma cells via p53 and DNA methyltransferase 1 (DNMT1), so as to participate in the occurrence and progression of glioma. Methods: LINC00467 expression in glioma was analyzed by GEPIA database and LINC00467 expression in glioma cell lines was detected by qRT-PCR. The regulatory effects of LINC00467 and p53 on proliferative, invasive capacities and cell cycle were conducted by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…15 LncRNA LINC00467 upregulation promotes glioma development through repressing P53 level. 16 Previous study showed that LINC00173 downregulation promotes non-small cell lung cancer cell growth and survival. 17 However, another study showed that Linc00173 enhances chemoresistance and facilitates tumor progression in small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…15 LncRNA LINC00467 upregulation promotes glioma development through repressing P53 level. 16 Previous study showed that LINC00173 downregulation promotes non-small cell lung cancer cell growth and survival. 17 However, another study showed that Linc00173 enhances chemoresistance and facilitates tumor progression in small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This study conducted enrichment analysis of m 5 C regulator‐related factors, and the results showed that these factors were enriched in items such as DNA replication, chromosome segregation, nuclear division, cell cycle and P53 signalling pathway. It is reported that up‐regulated LINC00467 can bind to DNMT1 and inhibit p53 level and promote glioma cells proliferation and invasion 22 . Furthermore, lncRNA SNHG7 regulates p53 expression and arrests cell cycle in the G0/G1 phase of osteosarcoma by binding with DNMT1 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of LINC00467 has been identified in diverse tumors like hepatocellular carcinoma, glioma, and neuroblastoma 16,34,35 . Especially, upregulated LINC00467 exhibited oncogenic roles to promote cell proliferation or prevented cell apoptosis in lung adenocarcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%